2017
DOI: 10.21273/hortsci10603-16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Physiological-based, On-demand Irrigation System for Container-grown Woody Plants with Different Water Requirements

Abstract: Two sensor-based irrigation scheduling systems were compared for water use and plant growth in container-grown Green Velvet boxwood (Buxus sempervirens L. × B. microphylla Siebold & Zucc. var. koreana ‘Green Velvet’) and slender deutzia (Deutzia gracilis Siebold & Zucc). These crops were chosen because they have different water requirements during production. The two sensor-based irrigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…events, which may affect plant growth. The moisture deficit in traditional irrigation systems might approach or exceed the water buffering capacity, which results in little to no plant-available water (Nambuthiri et al, 2017). This appears to contradict the results of Warsaw et al (2009) somewhat, who found that even moderate moisture deficit had little to no effect on plant growth.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…events, which may affect plant growth. The moisture deficit in traditional irrigation systems might approach or exceed the water buffering capacity, which results in little to no plant-available water (Nambuthiri et al, 2017). This appears to contradict the results of Warsaw et al (2009) somewhat, who found that even moderate moisture deficit had little to no effect on plant growth.…”
Section: Resultsmentioning
confidence: 89%
“…Nambuthiri et al (2017) reported that the moderate moisture deficit created by on-demand irrigation systems improved WUE by reducing the water use and leachate volume without a negative effect on plant growth. A plant-based irrigation schedule improved irrigation efficiency in Hibiscus rosa-sinensis 'Cashmere Wind', oakleaf hydrangea (Hydrangea quercifolia 'Alice'), and slender deutzia (Deutzia gracilis) (Fulcher et al, 2012;Hagen et al, 2014;Nambuthiri et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Photosynthetic rate has been successfully used as an irrigation-scheduling basis to improve crop water use efficiency [24][25][26]. Photosynthetic rate is related to stomatal conductance and both are impacted by as well as impact leaf water potential.…”
Section: Introductionmentioning
confidence: 99%